2018
DOI: 10.1002/pd.5372
|View full text |Cite
|
Sign up to set email alerts
|

Interest of chromosomal microarray analysis in the prenatal diagnosis of fetal intrauterine growth restriction

Abstract: Objective The aim of this study is to evaluate the diagnostic utility of prenatal diagnosis using the chromosomal microarray analysis (CMA) for fetuses presenting with isolated or associated intrauterine growth restriction (IUGR). Method We retrospectively included all fetuses with IUGR referred for prenatal testing and studied by rapid fluorescence in situ hybridization (FISH), karyotype, and CMA. Results Among the 162 IUGR fetuses (78 associated and 84 isolated IUGR) included, 15 had an abnormal FISH result:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…In addition, women should be counselled about the risk of a genetic etiology even in the presence of “isolated” FGR (i.e. without associated fetal anomalies) 37,270,283‐285 . A recent meta‐analysis of 10 studies found that in cases of isolated FGR, chromosomal microarray had an incremental yield of 4% (95% CI, 1%–6%) over karyotyping: 17 of 376 fetuses with isolated FGR and normal karyotype had significant findings in microarray, most commonly 22q11.2 duplication, Xp22.3 deletion, and 7q11.23 deletion.…”
Section: What Kind Of Investigations Should Be Performed When Fetal Gmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, women should be counselled about the risk of a genetic etiology even in the presence of “isolated” FGR (i.e. without associated fetal anomalies) 37,270,283‐285 . A recent meta‐analysis of 10 studies found that in cases of isolated FGR, chromosomal microarray had an incremental yield of 4% (95% CI, 1%–6%) over karyotyping: 17 of 376 fetuses with isolated FGR and normal karyotype had significant findings in microarray, most commonly 22q11.2 duplication, Xp22.3 deletion, and 7q11.23 deletion.…”
Section: What Kind Of Investigations Should Be Performed When Fetal Gmentioning
confidence: 99%
“…37,270,[283][284][285] A recent meta-analysis of 10 studies found that in cases of isolated FGR, chromosomal microarray had…”
mentioning
confidence: 99%
“…There have been few studies about what factors would influence the detection rate of CMA in fetuses with FGR. Since the commercial explosion of CMA, most studies of CMA in FGR focused on the incremental yield compared karyotype ( Borrell et al, 2018 ), as well as compared the detection rate of CMA between isolated FGR and FGR combined with other structural abnormalities ( Zhu et al, 2016 ; Borrell et al, 2017 ; Brun et al, 2018 ). There were only a few studies on isolated FGR.…”
Section: Introductionmentioning
confidence: 99%
“…24 In contrast to this literature, Brun et al did not find any additional improvement of the CMA over karyotype in the case of isolated IUGR. 25 Their selection criteria focused on the severity of the IUGR (<3rd centile) but not on its early onset. 25 We note the absence of aneuploidies in our cohort; this can be explained by the first trimester Down screening test performed for all the patients.…”
Section: Discussionmentioning
confidence: 99%
“…25 Their selection criteria focused on the severity of the IUGR (<3rd centile) but not on its early onset. 25 We note the absence of aneuploidies in our cohort; this can be explained by the first trimester Down screening test performed for all the patients. When Doppler anomalies are present, they tend to point to a vascular origin of the IUGR.…”
Section: Discussionmentioning
confidence: 99%